miR-486 Promotes Capan-2 Pancreatic Cancer Cell Proliferation by Targeting Phosphatase and Tensin Homolog Deleted on Chromosome 10 (PTEN) - Xia, Lu; Song, Meiyi; Sun, Mengxue; Chen, Wei; Yang, Changqing (Frontiers in Genetics, 2019)
Introduction: Pancreatic cancer is one of the most malignant digestive system tumors. Currently, the treatment of pancreatic cancer cannot achieve the expected curative effect. MicroRNAs (miRNAs, miRs) participate in many biological and pathological processes. miR-486 was involved in many malignant tumors, however, the role of miR-486 in pancreatic cancer remains unclear. Material and methods: miR-486 mimic and inhibitor were transfected in Capan-2 cells to increase or decrease the expression of miR-486. Western blot was used to detect protein expression level. EdU proliferation assay and flow cytometry were applied to identify changes in proliferation. PTEN overexpression plasmid together with miR-486 mimic were used to determine if PTEN downregulation mediates the effects of miR-486. Results: Overexpression of miR-486 promoted the proliferation and cell cycle progression of Capan-2 cells. Conversely, the proliferation and cell cycle of Capan-2 cells were attenuated after inhibition of miR-486. Combined with bioinformatics prediction software and western blot, PTEN was identified as a downstream target gene of miR-486. The promotion of miR-486 on Capan-2 cell proliferation could be inhibited by PTEN overexpression. Conclusions: miR-486 promotes the proliferation of Capan-2 cells by targeting PTEN. Inhibition of miR-486 might be a novel therapy for pancreatic cancer.